Mathematical Disposition of Slow Learners’ Conceptual Understanding using Bruner’s Theory - Wahidin Wahidin; Nurainy Dwi Novitasari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to analyze the relationship between mathematical disposition on the slow learners’ understanding of mathematical concepts in mathematics based on Bruner’s theory. This study used a qualitative method with a descriptive approach. The subjects were five slow learner students at Junior High School 3 Ciawigebang. Data were collected by documentation, tests and interviews. The results of the study revealed that there was a relationship between mathematical disposition and understanding of mathematical concepts of slow learner students in answering questions using Bruner’s theory, namely the symbolic and the iconic stages. Slow learners with a high level of mathematical disposition can solve all questions correctly and have met the indicators of understanding the mathematical concepts used in this study. Meanwhile, the slow learner with a moderate mathematical disposition can solve the questions given, but still have misconceptions in responding to some questions. Then, slow learners with a low mathematical disposition only understand some of the questions and have misconceptions in solving the question.